2009
DOI: 10.1007/s00284-009-9502-z
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of Lipid A Modification, RNA Degradation, and Central Intermediary Metabolism Facilitate the Growth of Legionella pneumophila at Low Temperatures

Abstract: Legionella pneumophila is an aquatic bacterium that is also the agent of Legionnaires' disease pneumonia. Since L. pneumophila is transmitted directly from the environment to the lung, it is important to understand how legionellae survive at low temperatures. To identify genes that are needed for L. pneumophila growth at low temperature, we screened a population of mutagenized legionellae for strains that are specifically impaired for growth at 17°C. From the 7400 mutants tested, eleven displayed defects rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…The T2S mutants are not impaired for entry into the amoebae, indicating that T2S is promoting bacterial resistance to intracellular killing and/or facilitating replication itself (22). Others of our studies have shown that T2S also promotes the persistence of L. pneumophila in the environment by facilitating extracellular survival in low-temperature water samples (18,(22)(23)(24)(25). Furthermore, L. pneumophila T2S helps to mediate the secretion of a surfactant that confers both sliding motility and antibacterial activity (26,27).…”
mentioning
confidence: 88%
“…The T2S mutants are not impaired for entry into the amoebae, indicating that T2S is promoting bacterial resistance to intracellular killing and/or facilitating replication itself (22). Others of our studies have shown that T2S also promotes the persistence of L. pneumophila in the environment by facilitating extracellular survival in low-temperature water samples (18,(22)(23)(24)(25). Furthermore, L. pneumophila T2S helps to mediate the secretion of a surfactant that confers both sliding motility and antibacterial activity (26,27).…”
mentioning
confidence: 88%
“…23,2010 LEGIONELLA PATHOGENESIS 283 17°C, and these included mutants with insertions into components of the T2SS. Other major factors included a homologue of the LpxP lipid A acyltransferase; an RNA helicase, CsdA, which was particularly important for bacterial survival; and RNase R, which was implicated previously in replication at low temperatures (70,309). Recently, L. pneumophila was observed to undergo sliding motility on agar plates, and this phenotype was linked to the function of the Lsp secretion system (323).…”
Section: The Lsp Type II Secretion Systemmentioning
confidence: 99%
“…T2S substrates first translocate across the inner membrane and into the periplasm by the Sec or Tat pathway, and then a pseudopilus acts to push the proteins through a dedicated outer membrane pore (27,58). For environmental L. pneumophila, an intact T2S system (known as Lsp) is required for both intracellular growth in amoebal hosts and extracellular survival in lowtemperature water samples (27,52,61,106). Following their intratracheal inoculation into A/J mice, lsp mutants do not increase in numbers in the lung, indicating that Lsp is also critical for L. pneumophila infection of and pathogenesis in mammalian hosts (27,34,96).…”
mentioning
confidence: 99%